An assessment of health care and economic growth in Sudan: an ARDL bound testing approach - Sirag, Abdalla; Adamu, Peter; Mohamed Nor, Norashidah (International Institute for Science, Technology & Education, 2013)
This study examined the long run and short run relationship between health care and economic growth in Sudan. Health care is represented by life expectancy and economic growth by GDP per capita. The study covers the period 1980-2010 and data retrieved from world development indicators of the World Bank. Aside from the theoretical variables and the main variables for this study, some other controlled variables such as expenditure on education and population growth were included in the model. The bounds testing approach for co-integration, Autoregressive Distributed Lag (ARDL) was applied in order to test for long run equilibrium between health care and economic growth. Additionally, Granger causality test was used to assess the causal relationship between health care and GDP per capita. The findings provide strong evidence that health care is positively related to economic growth in the long and short runs. The estimated Granger causality outcomes revealed a unidirectional relationship running from health care to GDP per capita. This is an indication that health care is very significant to economic growth in Sudan and efforts need to be geared towards improving the health status of the people for continuous economic growth and development in Sudan.